2018
DOI: 10.1016/j.insmatheco.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of common practice procedures in the fair evaluation of embedded options in insurance contracts

Abstract: This work analyses the common industry practice used to evaluate financial options written on with-profit policies issued by European insurance companies. In the last years regulators introduced, with the Solvency II directive, a market consistent valuation framework for determining the fair value of asset and liabilities of insurance funds. A relevant aspect is how to deal with the estimation of sovereign credit and liquidity risk, that are important components in the valuation of the majority of insurance fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…where Y I is a standard Brownian motion, assumed to be independent from the Brownian motions driving the dynamics of the risk-free rate and the credit spread and ϕ I (t) is a deterministic function of time that allows a perfect fitting of the initial ZCB prices of the specific issuer. As highlighted in [Gambaro et al, 2017], the possibility of having a negative liquidity spread is relevant for capturing the so called fly-to-liquidity effects. If we assume that the liquidity spread is independent from both the risk free rate and the credit spread, then, simply, the ZCB formula contains a second multiplicative adjustment factor in closed form.…”
Section: Sovereign Zero Coupon Bond Pricing Formulamentioning
confidence: 99%
See 3 more Smart Citations
“…where Y I is a standard Brownian motion, assumed to be independent from the Brownian motions driving the dynamics of the risk-free rate and the credit spread and ϕ I (t) is a deterministic function of time that allows a perfect fitting of the initial ZCB prices of the specific issuer. As highlighted in [Gambaro et al, 2017], the possibility of having a negative liquidity spread is relevant for capturing the so called fly-to-liquidity effects. If we assume that the liquidity spread is independent from both the risk free rate and the credit spread, then, simply, the ZCB formula contains a second multiplicative adjustment factor in closed form.…”
Section: Sovereign Zero Coupon Bond Pricing Formulamentioning
confidence: 99%
“…These market-consistent evaluations are mostly carried out in practice by applying the Certainty Equivalent approach (CEQ) in discounting expected cash flows, which implies adjusting contractual cash flows for the implied risk premium above the risk-free rate provided by EIOPA (see [CFO-Forum, 2016a] and [EIOPA, 2017]). The paper [Gambaro et al, 2017] has shown how this approach can lead to biased results in the valuation of contractual financial options in traditional insurance products where the pay-off is determined by statutory accounting rules. Another important aspect affecting market consistent valuations, is the rigid interpretation of market-consistency, which very often restricts the instruments to which stochastic models are calibrated to few categories of options such as interest rate swaps and equity indexes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In theory, the Esscher transform accounts for the basic hypothesis of options, which is the possibility of risk-free arbitrage. This method can be used to simulate a variety of statistical distributions, which makes options pricing more widely applicable [23].…”
Section: Introductionmentioning
confidence: 99%